Evaluation of Motility, Viability and Abnormality of Boar Spermatozoa in Various Modified Extenders - Hermilinda Parera; Victor Lenda (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2023)
The purpose of this study was to conduct an assessment on the quality of pig semen spermatozoa during storage and determine which diluent material should be used and how long pig semen can be stored. Freshly ejaculated boar semen was obtained from a two-years-old Duroc male and was diluted with Beltsville Thawing Solution (BTS) and Tris Citrate Fructose (TCF) supplemented with 5% egg yolk (KT) and extract of Borassus flabellifer Linn mesocarp (EM) 0.01% and stored at 13°C for up to 4 days. An experimental study with a completely randomized design with four groups and five repeats was applied. Parameters observed were motility, viability and abnormality of spermatozoa. Sperm quality was evaluated by examining motility and abnormality using a phase-contrast microscope with a magnification of 100X, and viability by eosin nigrosine staining. Parametric data were analyzed with ANOVA followed by Duncan test. The results showed that the supplementation of 5% egg yolk in the BTS diluent-based treatment group showed a higher percentage of motility (P<0.05) than without egg yolk, while the TCF-based diluent group showed no differences (P<0.05). Modified-Tris Citrate Fructose diluent supplemented with 5% egg yolk and 0.01% mesocarp extract was able to maintain a significantly higher percentage of viability (67.50±2.0) (P<0.05) than other groups, and had a percentage of abnormalities (9.75±0.957), significantly lower (P<0.05) than other groups. It was concluded that the modification of diluent TCF with 5% egg yolk and mesocarp extract 0.01% provide the best results in maintaining sperm quality with the highest percentage of sperm motility and viability, and the lowest percentage of sperm abnormality compared to the other three diluents. Likewise, all groups of modified-BTS and TCF diluent supplemented with 5% egg yolk and extract of Borassus flabellifer Linn mesocarp in this study were able to maintain motility >40%, viability >45% and abnormalities <20% so they were appropriate for using in the AI procedure.